The Ottoman mobilization of manpower in the First World War : between voluntarism and resistance - Beşikçi, Mehmet. (The Ottoman Empire and its Heritage, 2012)
The Ottoman Mobilization of Manpower in the First World War offers a multi-faceted story of how the Ottoman Empire tried to cope with the challenges of permanent mobilization under total war conditions which reshaped state-society relations. By focusing mainly on Anatolia and the Muslim population, Mehmet Beşikçi argues that the conditions of mobilization pushed the Ottoman state to become more centralized, authoritarian and nationalist, but the increasing dependence on people paradoxically also enlarged their space of action vis-à-vis state authority. The book demonstrates that people's responses to the state's needs constituted a wide spectrum ranging from voluntary support to open resistance such as desertion. In turn, the state responded by revising its mobilization policies and reformulating new mechanisms of control at the local level.